2022
DOI: 10.1136/bjophthalmol-2021-320892
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, causes and risk factors of vision loss in rural Southern China: 6-year follow-up of the Yangxi Eye Study

Abstract: PurposeTo report the 6-year incidence, causes and risk factors for vision loss (visual impairment (VI) and blindness), among elderly adults in rural southern China.MethodsPopulation-based, cohort study. Initiated in 2014, the study recruited participants aged 50 and older using random cluster sampling from Yangxi County. All eligible participants were invited to attend interviews and comprehensive eye examinations at the 6-year follow-up between November 2020 and March 2021. The WHO categories of vision loss w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Medical AI models are developed mainly for clinical application to fulfill unmet clinical needs, especially in rural areas. Recently, a few studies have investigated the incidence and prevalence of vision loss in rural areas, such as the Yangxi Eye Study 18 and the Handan Eye Study 21 in China and the Andhra Pradesh Eye Disease Study in India. 22 They found that patients in rural areas have great health care demands but experience the consequences of a lack of health awareness and poor access to high-quality and affordable eye services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical AI models are developed mainly for clinical application to fulfill unmet clinical needs, especially in rural areas. Recently, a few studies have investigated the incidence and prevalence of vision loss in rural areas, such as the Yangxi Eye Study 18 and the Handan Eye Study 21 in China and the Andhra Pradesh Eye Disease Study in India. 22 They found that patients in rural areas have great health care demands but experience the consequences of a lack of health awareness and poor access to high-quality and affordable eye services.…”
Section: Discussionmentioning
confidence: 99%
“…Yangxi County roughly reflects the eye health condition of rural residents and medical resources in low-income rural areas in China . Participants in this study were enrolled from the 6-year follow-up study of the Yangxi Eye Study, which was initiated in 2014 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuo et al 27 reported that family history was significantly higher in accommodative/partially accommodative esotropia and intermittent/constant exotropia than infantile esotropia. Also, probably because of the relatively inadequate eye care system in China, 28 potential patients with strabismus, especially older adults, are often undiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were identified using random cluster sampling, details of which are described elsewhere. 18,19 Persons aged 50 years or older living in the catchment area for at least 6 months were considered eligible. Eligible persons were invited to a nearby temporary research clinic for comprehensive eye examinations, a physical examination, and questionnaires.…”
Section: Study Populationmentioning
confidence: 99%